Ghana : Combined First and Second Reviews Under the Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of Performance Criteria, Modification of Performance Criteria and Rephasing of Disbursements; Staff Report; Staff Statement and Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Ghana. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Ghana's growth of 3-4 percent in 2009 was about twice the estimated average for sub-Saharan Africa. Fiscal performance in 2009 was weaker than programmed, giving rise to substantial new domestic expenditure arrears. The Bank of Ghana (BoG) eased monetary conditions as inflationary pressures receded. Progress in reinvigorating structural reforms gained momentum through end-2009. Growth is projected to strengthen to 4-5 percent in 2010. For 2010, the authorities are targeting a budget deficit of 8 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet